Significant association of a M129V independent polymorphism in the 5′ UTR of the PRNP gene with sporadic Creutzfeldt-Jakob disease in a large German case-control study. Issue 10 (17th October 2006) - Vollmert, C; Windl, O; Xiang, W; Rosenberger, A; Zerr, I; Wichmann, H-E; Bickeböller, H; Illig, T; Kretzschmar, H A
Abstract : Background: A single nucleotide polymorphism (SNP) in the coding region of the prion protein gene ( PRNP ) at codon 129 has been repeatedly shown to be an associated factor to sporadic Creutzfeldt-Jakob disease (sCJD), but additional major predisposing DNA variants for sCJD are still unknown. Several previous studies focused on the characterisation of polymorphisms in PRNP and the prion-like doppel gene ( PRND ), generating contradictory results on relatively small sample sets. Thus, extensive studies are required for validation of the polymorphisms in PRNP and PRND . Methods: We evaluated a set of nine SNPs of PRNP and one SNP of PRND in 593 German sCJD patients and 748 German healthy controls. Genotyping was performed using MALDI-TOF mass spectrometry. Results: In addition to PRNP 129, we detected a significant association between sCJD and allele frequencies of six further PRNP SNPs. No significant association of PRND T174M with sCJD was shown. We observed strong linkage disequilibrium within eight adjacent PRNP SNPs, including PRNP 129. However, the association of sCJD with PRNP 1368 and PRNP 34296 appeared to be independent on the genotype of PRNP 129. We additionally identified the most common haplotypes of PRNP to be over-represented or under-represented in our cohort of patients with sCJD. Conclusion: Our study evaluated previous findings of the association of SNPs in the PRNP and PRND genes in the largest cohorts for association study in sCJD to date, and extends previous findings by defining for the first time the haplotypes associated with sCJD in a large population of the German CJD surveillance study.